Water Quality Assessment Models for Dokan Lake Using Landsat 8 OLI Satellite Images - Abdullah, Hasti Shwan; Mahdi, Mahmoud S.; Ibrahim, Hekmat M. (Sulaimani Journal for Pure and Applied Sciences, 2017)
It is impractical to monitor water quality more than a small fraction of lakes by conventional field methods because of expense and time requirements. Satellite image is more convenient to be applied to collect the required data for monitoring and assessing water quality in the lakes. Therefore, this study aims to estimate the concentration of some water quality parameters (Temperature, DO, BOD, pH, Turbidity, TSS, TDS, EC, NO3, PO4 and E. coli) by applying developed models based on the remote sensing and GIS techniques on the Landsat 8 OLI satellite image using twenty points in Dokan lake, Kurdistan Region, Iraq at two different seasons. Multiple linear regression is used to obtain mathematical models for estimating the concentration of some water quality parameters depending on spectral reflectance of Landsat 8 OLI. In this study, new band (coastal blue) of Landsat 8 OLI has been undertaken in developing of models. Moreover, new Independent Component Analysis (ICA) and new 7 band ratios with 16 band combinations have been used. The best models are obtained for TSS, Turbidity and DO with coefficient of determination (R2 ) of 0.98, 0.98, and 0.83 respectively. Generally, for spring season, the performance of all models is reduced due to seasonal change, variance of parameters and other factors. However, high R2 of 0.86 has been shown for Temperature. The results of the developed WQPs models have been mapped to show the water quality parameters concentration distribution within Dokan lake. The conclusions present that correlation of all bands of Landsat 8 OLI is appropriate to water quality parameters.
Keywords: Dokan Lake; WQPs; Image Processing; Landsat 8; GIS